Evaluating the potential for pharmacists to prescribe oral anticoagulants for atrial fibrillation. (January 2018) - Sandhu, Roopinder K.; Guirguis, Lisa M.; Bungard, Tammy J.; Youngson, Erik; Dolovich, Lisa; Brehaut, Jamie C.; Healey, Jeff S.; McAlister, Finlay A.
Background: Oral anticoagulant therapy (OAC) to prevent atrial fibrillation (AF)–related strokes remains poorly used. Alternate strategies, such as community pharmacist prescribing of OAC, should be explored. Methods: Approximately 400 pharmacists, half with additional prescribing authority (APA), randomly selected from the Alberta College of Pharmacists, were invited to participate in an online survey over a 6-week period. The survey consisted of demographics, case scenarios assessing appropriateness of OAC (based on the 2014 Canadian Cardiovascular Society AF guidelines) and perceived barriers to prescribing. Regression analysis was performed to determine predictors of knowledge. Results: A total of 35% (139/397) of pharmacists responded to the survey, and 57% of these had APA. Depending on the case scenario, 55% to 92% of pharmacists correctly identified patients eligible for stroke prevention therapy, but only about a half selected the appropriate antithrombotic agent; there was no difference in the knowledge according to APA status. In multivariable analysis, predictors significantly associated with guideline-concordant prescribing were having the pharmacist interact as part of an interprofessional team ( p = 0.04) and direct OAC (DOAC) self-efficacy (confidence in ability to extend, adapt, initiate or alter prescriptions; p = 0.02). Barriers to prescribing OAC for APA pharmacists included a lack of AF and DOAC knowledge and preference for consulting the physician first, but these same pharmacists also identified difficulty in contacting the physician as a major barrier. Interpretation and Conclusion: Community pharmacists can identify patients who would benefit from stroke prevention therapy in AF. However, physician collaboration and further training on AF and guidelines for prescribing OAC are needed.